MEDIA PEMBELAJARAN KOGERBE (KOTAK GERAK BENDA) PADA MATERI GERAK BENDA MATA PELAJARAN IPA KELAS IV SEKOLAH DASAR - Cecilia Siadari; Lala Jelita Ananda (Universitas Negeri Medan, 2020)
Abstract: Learning Media Kogerbe (Box Motion Objects) on Object Motion Material for Class IV Elementary School Science Subjects. This study aims to develop learning media Kogerbe (Box Motion Objects) and to determine the feasibility of learning media Kogerbe (Box Motion Objects) on the subject matter Motion Objects Science Subject in grade IV SD Negeri 105335 Kebun Sayur. This research is a research and development or Research and Development (R&D). The development model used in this research is the ADDIE model using 5 steps, namely (analysis), design (design), development (development), implementation (implementation) and evaluation (evaluation). Validation was carried out by two experts, namely learning media experts and material experts and field testing (student responses). The results showed that the average score of media experts was 4.3 with a percentage of 85% in the category of